The Role and Function of Online Media in Improving Marketing Quality in the Ornamental Plant Business Based on Sharia Marketing Analysis - Muhammad Taufiqur Rohman; Anggoro Sugeng (Jurnal Internasional Ekonomi Islam, 2023)
The use of online media as a marketing medium in the ornamental plant business of Berkah Jaya Horticulture Garden is very influential in the business development process. Also, it has a massive role in expanding product marketing reach. This study aims to determine the role and function of online media in increasing the marketing of ornamental plants in the Berkah Jaya Horticulture Garden regarding Sharia marketing principles. This type of research uses field research, where the researcher goes directly to the field to examine the state of the phenomena that occur at the research site—in this study, using a descriptive qualitative approach. The study results found that the marketing practices carried out by Berkah Jaya Horticulture Gardens included promoting Berkah Jaya Horticulture Gardens using advertising and live streaming features, which were also for friendly media. The stages of ordering between the buyer and the seller are the contract assembly in the form of an online sales account, bai' al-hal contracts, ijarah contracts, and wakalah bi al-ujrah contracts. The packaging process by guaranteeing the quality of ornamental plants before they are sent is one way to prevent consumer losses. Delivery of ornamental plants in collaboration with freight forwarding providers has an ijarah contract. Service by providing a question and answer column in the sales account, responding to complaints that come in very carefully, and granting the right of payment to warranty service.